SELEKSI CALON PENERIMA BEASISWA PT. ADIMITRA BARATAMA NUSANTARA MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Bedi Suprapty; Lia Dwi Utami; Arief Bramanto Wicaksono Putra (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2019)
PT. Adimitra Baratama Nusantara is a coal company in Sangasanga that provides scholarship funds to students in Sangasanga. The large number of scholarship registrants makes it difficult for companies to handle data processing, so software is needed to facilitate the processing of the data. This research was conducted with the aim of constructing a decision model to determine the scholarship recipients using the SAW method so that the selection process for prospective scholarship recipients can be completed precisely, quickly, and more procedurally. Determination of scholarship recipients is determined from several criteria, among others; parents' income, number of family members, home electrical power, average report card grade, class, and extracurricular numbers followed. Then to design an application requires several stages, namely by making Context Diagrams, Data Flow Diagrams, and Entity Relationship Diagrams and applying them to a software / program that will be built using Visual Basic 6 programming language along with Microsoft Access database. Decision model for scholarship recipients at PT. Adimitra Baratama Nusantara with the Simple Additive Weighting (SAW) Method resulted in 10 applicants being selected as scholarship recipients and 20 applicants declared to have failed the selection process